Influence of thermal pretreatments on dimensional change and humidity sensitivity of densified spruce and poplar wood - Pelit, Huseyin; Yorulmaz, Ramazan (Maderas. Ciencia y Tecnología, 2023)
Densification modification is an effective method to improve many properties of wood. However, den- sified wood is sensitive to humidity and is not dimensionally stable. The effect of thermal pretreatments on the dimensional change and humidity sensitivity of densified Picea orientalis (spruce) and Populus nigra (poplar) wood were investigated. A thermal pre-treatment was applied on the wood specimens at 140 °C, 160 °C, 180 °C, and 200 °C for 7 h and 9 h. Wood specimens were then compressed at ratios of 20 % and 40 % at a temperature of 150 °C. The results showed that spring-back and thickness swelling increased in all specimens (thermally pre-treated and untreated) depending on the increase in compression ratio. However, set recovery was determined higherat 20 % compression ratio.The equilibrium moisture content values of untreated specimens and thermally pre-treated specimens at low temperatures (140 ºC and 160 ºC) were found lower than uncompressed specimens. The impact of compression ratio on equilibrium moisture content was not clear. Thermal pretreatments significantly affected the dimensional stability and hygroscopicity of densified specimens (especially poplar wood). Depending on the increase in thermal pre-treatment temperature and du- ration, spring-back, set-recovery and thickness swelling in wood specimens decreased up to 31 %, 67 % and 62 %, respectively. In addition, equilibrium moisture content and water absorption decreased with the increase in thermal pre-treatment temperature and duration. Moreover, the thermal treatment temperature was more important than duration on the investigated properties.